The use of augmentative and alternative communication in Cyprus: Findings from a preliminary survey - Pampoulou, Eliada; Theodorou, Elena; Petinou, Kakia (My University, 2018)
Whilst augmentative and alternative communication has been used for over sixty years across many countries, in Cyprus it remains underdeveloped. The current study seeks to investigate the current AAC practices in Cyprus. Data were collected through electronically distributed questionnaires to all registered speech and language therapists (n = 330), contacted by the Cyprus Speech Therapy Association. The questionnaire comprised 12 questions, which were categorized into three sections: background information (educational level and clinical experience), training undergone (during or after completion of tertiary education) and participants’ AAC practices (caseload, assessment and intervention). The findings from the analysis of the returned data (n = 59) reveal that training provision on augmentative and alternative communication has positively influenced practice. Most of the participants received training in the specific field during their bachelor’s degree, rather than during later education. Life-long training on different language systems (including different assistive technology tools, such as symbols and talking products as well as methods such as the Picture Exchange Communication System) also played a pivotal role in their work. Regarding the assessment process, the findings show that whilst there are a number of standardized language assessment tools, the participants relied heavily on non-standardized tools and/or their clinical judgment. Regarding intervention, they reported using different language systems and a variety of Assistive Technology equipment. Several recommendations are made aimed at raising the profile of AAC services in Cyprus, especially with regards to training and assessment, as the findings show that these areas have not been addressed systemically thus far.
Keywords: Augmentative and alternative communication; Cyprus; People with complex communication needs; Speech and language therapy